EFFECT OF ORGANIC FARMING PRACTICES ON YIELD AND QUALITY OF CABBAGE (Brassica oleracea Brassica oleracea Brassica oleracea Var. capitata capitata L.) - M. PRABHAKAR; S. S. HEBBAR; A. K. NAIR; . PANNEER SELVAM; .S.SHIVASHANKARA; G.A.GEETHA; R.S.RAJESHWAR; PRAVEEN KUMAR (The Bioscan, 2019)
An experiment was conducted in organic vegetable experimental field of IIHR farm, Hesaraghatta, Bengaluru to study the effect of different levels of organic manure in organically and conventionally grown cabbage (Brassica oleracea var. capitata L.) for fruit yield, quality and soil microbial status. The trial included five organic manure treatments comprising 25, 50, 75, 100% of recommended dose of nitrogen equivalent of FYM and recommended FYM i.e. 25t/ha) and two inorganic nutrient treatments viz; recommended FYM @ 25 tonnes/ha + recommended NPK fertilizers and only recommended NPK. The treatment which received recommended FYM + NPK fertilizers produced highest yield of 60.8 t/ha followed by the treatment which received 100% of recommended dose of nitrogen (RDN) through organic manure (50.9 t/ha). The lower head yield of 44.7 and 45.6 t/ha were observed with application of only FYM (25 t/ha) and only NPK fertilizer treatments. Yield attributing parameters like polar circumference (41.8 cm), equatorial circumference (49.8 cm) were higher in treatment which received the recommended FYM+ NPK fertilizers. Higher yields with better quality heads were attained with integrated nutrient management and organic treatments as compared to crop grown with only chemical fertilizers.